2021
DOI: 10.3390/cells10061343
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Developmentally Essential Secreted Peptides Such as Thymosin Beta-4 to Remind the Adult Organs of Their Embryonic State—New Directions in Anti-Aging Regenerative Therapies

Abstract: Our dream of defeating the processes of aging has occupied the curious and has challenged scientists globally for hundreds of years. The history is long, and sadly, the solution is still elusive. Our endeavors to reverse the magnitude of damaging cellular and molecular alterations resulted in only a few, yet significant advancements. Furthermore, as our lifespan increases, physicians are facing more mind-bending questions in their routine practice than ever before. Although the ultimate goal is to successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 134 publications
0
1
0
Order By: Relevance
“…As the main sequestering protein family of G-actin, the beta-thymosin family is an important peptide hormone secreted by the subcapsular TECs [ 13 ], which can play a key regulatory role in the immune system by paracrine means, especially in controlling the development and function of T lymphocytes [ 14 , 15 ]. Recent advances in thymus biology have indicated that the complex three-dimensional (3D) network of TECs involves the biological processes of muscle-like contractions, such as actin and myosin [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the main sequestering protein family of G-actin, the beta-thymosin family is an important peptide hormone secreted by the subcapsular TECs [ 13 ], which can play a key regulatory role in the immune system by paracrine means, especially in controlling the development and function of T lymphocytes [ 14 , 15 ]. Recent advances in thymus biology have indicated that the complex three-dimensional (3D) network of TECs involves the biological processes of muscle-like contractions, such as actin and myosin [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%